Роль изменений структурнофункционального состояния мембраны эритроцита в развитии анемии у больных раком желудка - Гунина, Л.М.; Кабан, А.П.; Коробко, В.Б. (Онкологія, 2000)
Обследовали 65 больных раком желудка в целях изучения роли мембраны эритроцита в развитии анемии. Установлено, что при развитии злокачественной опухоли происходит активация перекисного окисления липидов с нарушением функционального состояния мембраны эритроцита и уплотнением гликокаликса. При этом изменяется проницаемость мембраны эритроцита и его объем, значительно повышается степень анизоцитоза, что сопровождается снижением концентрации гемоглобина в красных клетках крови и развитием анемии. Sixty five gastric cancer patients were examined with the view to study the role of erythrocyte membranes in the development of anemia. It was found that the development of malignant tumors is associated with activation of peroxide oxidation of lipids; functional alterations in the state of erythrocyte membranes; and consolidation of the adjacent membrane layers in cytosole. In addition, the level of penetrability of erythrocyte membranes and the volume of erythrocytes change and these changes are accompanied by a significant increase in the anisocytosis index and a decrease in the hemoglobin content in red blood cells.